Sign Language Variations in Kata Kolok - Putri, Dian Rahmani; Sutjaja, IGM; Mbete, Aron Meko; Pastika, I Wayan (e-Journal of Linguistics, 2018)
The study focuses on sign language namely kata kolok, which is naturally used in Bengkala village, Buleleng, Bali, by the local deaf community, specifically on their idea and thought to describe their religious living, customs and culture. The aim of this research is to enrich references of a sign language system contributed by sign language owned by the Kolok community in Bengkala. The data obtained is primary, qualitative; those are lexicon, expression, sentences, text in the form of sign language. The data were collected by observation, video recording and direct interviewing by using new etnography approach or cognitive anthropology. The data analysis is conducted by content analysis. In the future, this research is expected to generate a Kata Kolok Dictionary, a comprehensive documentation and effective information dedicated to the signer or the sign language user, and also as the preservation of Kata Kolok as the natural sign language. There are sign and meaning variations found, such as sign variations for the 3 rd  person singular pronoun, modality ‘have to’, religious-signs ‘mabanten’ and ‘Pura’, the customs sign ‘ngaben’, culture sign ‘tajen’, survival sign ‘talking’, and  emotional expression ‘sad’ and ‘surprised’. Furthermore, there are phenomena such as homonymy and polysemy for some meanings.       Keywords : meaning and sign, variation, homosign, polysemy, sign language, Kata Kolok